Nanocharacterization techniques - Leite, Fabio de Lima; Ferreira, Marystela; Oliveira, Osvaldo N.; Roz, Alessan Luzia Da (Micro and nano technologies series, 2017)
Nanocharacterization Techniques covers the main characterization techniques used in nanomaterials and nanostructures. The chapters focus on the fundamental aspects of characterization techniques and their distinctive approaches. Significant advances that have taken place over recent years in refining techniques are covered, and the mathematical foundations needed to use the techniques are also explained in detail. This book is an important reference for materials scientists and engineers looking for a through analysis of nanocharacterization techniques in order to establish which is best for their needs.